ANALISIS KINERJA KEUANGAN PADA SMPS YPMNU BINA BAKTI WANITA TIMIKA - Ilham Masis; Tuti Fitriani (CV. Adiba Aisha Amira, 2025)
Abstract This research aims to determine financial performance in terms of fiscal performance, non- program activity efficiency performance, and program efficiency performance. This research is descriptive research with data collection techniques using documentation and interview techniques. The data analysis instrument used is the financial ratios of non-profit organizations including fiscal performance, non-program activity efficiency performance, and program efficiency performance. The results of the analysis show that financial performance in terms of fiscal performance for total income divided by total costs can be said to be quite good with an increase of 1% from 2020 to 2021 and there is no increase in performance from 2021 to 2022 while for total income divided by total assets it can be said in the good category with an increase of 2% and 11% from year to year, the efficiency performance of non-program activities is less efficient with a decrease of 6% from 2020 to 2021 and an increase of 1% from 2021 to 2022, the efficiency performance of the program is less efficient with a decrease 6% from 2020 to 2021 and no increase in performance from 2021 to 2022.